Comparative effectiveness of tildrakizumab 200 mg versus tildrakizumab 100 mg in psoriatic patients with high disease burden or above 90 kg of body weight: a 16-week multicenter retrospective study - IL PSO (Italian landscape psoriasis) - Luigi Gargiulo; Luciano Ibba; Ruggero Cascio Ingurgio; Piergiorgio Malagoli; Fabrizio Amoruso; Anna Balato; Federico Bardazzi; Pina Brianti; Giovanna Brunasso; Martina Burlando; Anna E. Cagni; Marzia Caproni; et al. (Taylor & Francis Group, 2024)
AbstractPurpose Tildrakizumab is a selective inhibitor of IL-23 approved for the treatment of moderate-to-severe plaque psoriasis in two dosages. We conducted a 16-week multicenter retrospective study to compare the effectiveness and safety of tildrakizumab 200 mg versus tildrakizumab 100 mg in patients with a high disease burden or high body weight.Materials and methods Our retrospective study included 134 patients treated with tildrakizumab 200 mg and 364 patients treated with tildrakizumab 100 mg from 28 Italian Dermatology Units affected by moderate-to-severe plaque psoriasis. The patients had a body weight above 90 kg or a high disease burden (Psoriasis Area and Severity Index [PASI] ≥ 16 or the involvement of difficult-to-treat areas). We evaluated the effectiveness of tildrakizumab at the week-16 visit in terms of PASI90, PASI100 and absolute PASI ≤ 2.Results After 16 weeks of treatment with tildrakizumab 200 mg, PASI90 was reached by 57.5% of patients and PASI100 by 39.6% of patients. At the same time point, 34.3% and 24.2% of patients treated with tildrakizumab 100 mg achieved PASI90 and PASI100, respectively.Conclusions Our data suggest that tildrakizumab 200 mg has better effectiveness than tildrakizumab 100 mg in patients with a body weight ≥ 90 kg and a high disease burden.